Electroacupuncture for treating insomnia in patients with cancer: a study protocol for a randomised pilot clinical trial. Issue 8 (11th August 2017) - Kim, Mikyung; Kim, Jung-Eun; Lee, Hye-Yoon; Kim, Ae-Ran; Park, Hyo-Ju; Kwon, O-Jin; Kim, Bo-Kyung; Cho, Jung Hyo; Kim, Joo-Hee
Abstract : Introduction: Although insomnia is one of the most prevalent and disturbing symptoms among patients with cancer, it has not been properly managed. Electroacupuncture (EA) has received attention as a promising intervention for insomnia, and a few previous studies have reported that this intervention may be beneficial for treating insomnia in patients with cancer. The aim of this pilot study is to explore the feasibility and preliminary effectiveness of EA on the sleep disturbance of patients with cancer with insomnia using a subjective method, patient-reported questionnaires and an objective tool, actigraphy, to measure the quality of sleep. Methods and analysis: This is a study protocol for a randomised, three-arm, multicentre, pilot clinical trial. A total of 45 patients with cancer who have continuous insomnia related to cancer treatment or cancer itself will be randomly allocated to an EA group, sham EA group or usual care group in equal proportions. The EA group will receive 10 sessions of EA treatment over 4 weeks. The sham EA group will receive sham EA at non-acupoints using non-penetrating Streitberger acupuncture needles with mock EA. The usual care group will not receive EA treatment. All participants will be provided a brochure on the management of sleep disorders regardless of their group assignment. The primary outcome measure is the mean change in the insomnia severity index from the baseline to week 5. Information related to sleep quality will also be obtained through the Pittsburgh Sleep Quality Index, a sleep diary and actigraphy. Participants will complete the trial by visiting the research centre at week 9 for follow-up assessment. Ethics and dissemination: This study protocol was approved by the institutional review boards of each research centre. Written informed consent will be obtained from all participants. The result of this study will be published in peer-reviewed journals or presented at academic conferences. Trial registration number: KCT0002162; Pre-results.